Antiviral activity of silymarin in comparison with baicalein against EV-A71 - Lalani, S.*; Anasir, M. I. *; Poh, Chit Laa * (BMC (Part of Springer Nature), 2020)
Background: The hand, foot and mouth disease (HFMD) is a febrile and exanthematous childhood disease mainly caused by Enterovirus 71 (EV-A71). In severe HFMD, virulent EV-A71 strains can cause acute flaccid paralysis and cardiopulmonary edema leading to death. Currently, no FDA approved antiviral treatment or vaccine is available for EV-A71. Flavonoids such as silymarin and baicalein are known to possess in vitro antiviral properties against viruses. In this study, the cytotoxicity and antiviral activity of silymarin, baicalein and baicalin were investigated. Methods: The cytotoxic effects of three flavonoids towards rhabdomyosarcoma (RD) cells were first examined using cell proliferation MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] assay. Compounds found to be non-cytotoxic in RD cells were evaluated for their in vitro antiviral properties against the EVA71 subgenotype B4 strain 41 (5865/SIN/000009) using antiviral assays. Viral infectivity was determined by reduction of the formation of plaques in RD cells. For the measurement of RNA copy number, the real time quantitative reverse transcription PCR (qRT-PCR) was used. The most potent compound was further evaluated to determine the mode of action of inhibition by time course, virus attachment and entry assays in Vero cells. Results: Silymarin was shown to exert direct extracellular virucidal effects against EV-A71 at 50% inhibitory concentration (IC50) of 15.2 ± 3.53 μg/mL with SI of 10.53. Similarly, baicalein exhibited direct extracellular virucidal effects against EV-A71 at a higher IC50 value of 30.88 ± 5.50 μg/mL with SI of 13.64. Besides virucidal activity, silymarin was shown to block both viral attachment and entry of EV-A71 to inhibit infection in Vero cells. Conclusions: Silymarin has a stronger inhibition activity against EV-A71 in comparison to baicalein. It could serve as a promising antiviral drug to treat EV-A71 infections.